Morphological and Anatomical Characterization of Mature Culms of Guadua angustifolia Kunth as a Raw Material for Transformation Processes - Andres Prieto Muriel; Valentina Diaz Henao; Jorge Augusto Montoya Arango (BioResources)
The global bamboo market reached USD 70 billion in 2022, and moso bamboo (Phyllostachys edulis) is the species with the greatest international impact. Guadua (Guadua angustifolia Kunth) is a promising species, that has been traditionally used for the construction and manufacture of handcrafts in several countries in Central and South America. In this research, progress was made in the morphological and anatomical characterization of mature guadua culms. On average the culms are 21 m in total length and there are 53.2 kg of dry biomass. The culm morphology was characterized throughout its length; the average diameter, wall thickness, and density at breast height are 14.8 cm, 21.5 mm, and 0.595 g/cm3, respectively. The fibers of the vascular bundles of internode number 7 have an average length of 2146 µm, a diameter of 20.4 µm, and a diameter of 8.7 µm wall thickness. The morphological and anatomical characteristics of guadua offer productive and comparative advantages and could be competitive in the bamboo market. The research, technological development, and innovation processes related to this material should be encouraged to promote the guadua industry.